2007
DOI: 10.1359/jbmr.061115
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Indices of Bone Strength Are Associated With Physical Activity and Dietary Calcium Intake in Healthy Older Women

Abstract: A population-based study on 1008 postmenopausal women identified that the 24% of women achieving high levels of PA and CI had 3.4-4.4% higher femoral bone strength in axial compression and 1.7-5.2% in bending than those achieving low levels, indicating that lifestyle factors influence bone strength in the proximal femur. Introduction:Extensive research has shown that increased physical activity (PA) and calcium intake (CI) decrease the rate of bone loss; however, there is little research on how these lifestyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 35 publications
2
21
0
Order By: Relevance
“…bone strength index) measures of bone strength and PA in older adults populations. However, similar to our findings, Nurzenski et al (2007) and Uusi-Rasi, Sievä nen, Pasanen, Beck, and Kannus (2008) reported significant positive associations between aspects of femoral bone geometry and PA in older adults females, whereas there is only one report to our knowledge (Semanick et al, 2005), which likewise, indicated a weak positive relationship between walking and FN section modulus in older adults men.…”
Section: Discussionsupporting
confidence: 88%
“…bone strength index) measures of bone strength and PA in older adults populations. However, similar to our findings, Nurzenski et al (2007) and Uusi-Rasi, Sievä nen, Pasanen, Beck, and Kannus (2008) reported significant positive associations between aspects of femoral bone geometry and PA in older adults females, whereas there is only one report to our knowledge (Semanick et al, 2005), which likewise, indicated a weak positive relationship between walking and FN section modulus in older adults men.…”
Section: Discussionsupporting
confidence: 88%
“…These structural geometrical variables, demonstrated to be useful in the understanding of bone fragility, are also available from analysis of DXA hip images [14].…”
Section: Mindways Regression Equationmentioning
confidence: 99%
“…In their study Chaubber & Singh showed higher value of various parameters on left side than that of right, as whether a person is right handed or left handed, more people use left lower limb for more weight bearing [6]. A population based study by Nurzenski et al, showed that life style factors also influence geometric indices of bone strength in the proximal femur [7]. So, to minimise post operative complications the implants should be designed by taking into account the parameters of the local population.…”
Section: Introductionmentioning
confidence: 95%